Public Trust Reconstruction Strategy: The Case of the North Gorontalo Regency Government After the Re-Vote - Hanasi, Raihan A.; Isa, Rusli (Universitas Negeri Gorontalo, 2025)
The election of the Regent and Deputy Regent of North Gorontalo in 2024 is experiencing legal tension that has given rise to a Re-Vote (PSU). The uncertainty caused by this legal dispute has led to a decline in public trust in the democratic process and local government. This research aims to identify the strategies implemented by the North Gorontalo Regency Government in rebuilding public trust after PSU. The method used is a qualitative approach with case studies, where data is collected through in-depth interviews, direct observations, and documentation studies. The analysis was carried out thematically to outline the condition of public trust and evaluate government strategies. The results of the study show that local governments implement strategies of transparency, open communication, community involvement, and improving the quality of public services. Despite the challenges related to information disclosure and local political dynamics, these efforts have succeeded in restoring some of the public's trust. The research also provides recommendations for future policies, emphasizing the importance of effective communication and active community participation in strengthening public trust.